Tkáňově specifická mutageneze modelového organismu Drosophila melanogaster pomocí TAL nukleáz - Gregor, Tomáš (Jihočeská univerzita, 2015)
TAL nucleases are frequently used for mutagenesis in germline to create transgenic organism with mutation in every cell. I created TAL nucleases against eGFP and Drosophila AdoR receptor and combined them with UAS-Gal4 system to test if it is possible to use this genetic tool also for tissue specific mutagenesis.
Tissue specific mutagenesis with TAL nucleases using Drosophila melanogaster as a model